A new palaeontinid (Insecta, Hemiptera, Cicadomorpha) from the Upper Jurassic Tiaojishan Formation of northeastern China and its biogeographic significance. (May 2020) - Fu, Yanzhe; Cai, Chenyang; Huang, Diying
Abstract: Cicadomorpha guancaishanensis new species, of the extinct family Palaeontinidae, is described from the Upper Jurassic Tiaojishan Formation at Guancaishan, Jianping County, Western Liaoning, northeastern China. It represents the first record of Palaeontinidae from the Tiaojishan Formation and highlights the palaeodiversity of the Late Jurassic palaeontinids. Cicadomorpha Martynov, 1926 previously included three species with extremely limited morphological differences from the Karabastau Formation of Kazakhstan, the Glushkovo Formation, and the Ukurei Formation of Chita, Transbaikalia, and Russia, indicating a correlated stratigraphic relationship. This discovery provides new evidence that closure of the Okhotsk Ocean began in the Middle Jurassic. Thus, there is no distinct geographical barrier between the southern and northern areas of Mongolia-Okhotsk Ocean in the Late Jurassic. UUID: http://zoobank.org/64531de4-070c-43d4-ae01-106d4338027b .